The Effect of Pulmonary Hypertension on Left Ventricular Diastolic Function in Chronic Obstructive Lung Disease: A Tissue Doppler Imaging and Right Cardiac Catheterization Study - Acikel, Mahmut (Clin Cardiol, 2010)
BACKGROUND: Pulmonary hypertension (PH) caused by chronic obstructive lung disease (COLD) essentially involves the right heart. Also left ventricular (LV) systolic and diastolic functions may be affected. OBJECTIVES: The aim of this study was to investigate the effect of on LV diastolic function in patients with COLD. METHODS: A total of 47 patients with COLD and 20 controls were included in this study. All patients underwent Doppler echocardiography, tissue Doppler imaging examinations and right cardiac catheterization. The patients were divided into 2 subgroups according to mean pulmonary arterial pressure (mPAP): patients without PH (group1, n = 25) and with PH (group 2, n = 22). The following measurements were taken: peak velocity of early diastolic filling (E), peak late filling with atrial contraction (A), E/A ratio, deceleration time (DT) of E, isovolumic relaxation time (IVRT), early (Em) and late (Am) diastolic mitral lateral annulus velocity. RESULTS: Mitral E/A < 1 and Em < 8 cm/sec were higher in group 2 than in group 1 and the control group. There were significant correlations between mPAP and both mitral E/A (r:− 0.60) and Em (r:− 0.45). In multivariate model, mPAP was not found to be significant on mitral E/A ratio < 1, but there was a significant effect on mitral Em < 8 cm/sec (odds ratio [OR]:1.14, P < 0.05). CONCLUSION: This study shows that LV diastolic dysfunction in COLD is closely correlated to PH levels. Although increased mPAP may affect the mitral E/A ratio, it seems to have no effect on mitral E/A < 1, whereas it has an independent effect on Em < 8 cm/sec. Copyright © 2010 Wiley Periodicals, Inc.